Iron Deficiency and the Risk of Incident Left Ventricular Dysfunction in Patients with Coronary Artery Disease: A Single-center Cohort Study - Chiao-Hsiang Chang; Chiao-Chin Lee; Shi-Chue Hsing; Hsin-Hui Chen; Yu-Lan Liu; Wei-Ting Liu (Journal of Medical Sciences)
Background: Heart failure (HF) is a complex and life-threatening condition that often coexists with comorbidities such as hypertension, type 2 diabetes mellitus, coronary artery disease (CAD), and iron deficiency (ID). However, the relationship between ID and the development of HF remains poorly understood. Aim: This study aimed to investigate the correlation between ID and the development of left ventricular dysfunction. Methods: A total of 64,661 patients diagnosed with CAD at a tertiary hospital between 2011 and 2023 were recruited. Of these, 4813 patients who underwent iron status evaluation, including serum iron (SI), total iron-binding capacity (TIBC), and ferritin within 30 days, were included in the analysis. We compared the incidence and hazard ratio (HR) of new-onset left ventricular (LV) dysfunction (LV ejection fraction <50%) between patients with and without ID, defined as SI/TIBC or transferrin saturation (TSAT) <20% or ferritin <100 ng/mL. Results: The incidence of new-onset LV dysfunction was higher in patients with ID, defined by TSAT <20% compared to those with normal TSAT (HR, 1.40; 95% confidence interval [CI], 1.14–1.72) over a 13-year follow-up. In multivariable analysis, TSAT <20% retained its predictive value for new-onset LV dysfunction (adjusted HR, 1.24; 95% CI, 1.01–1.54), while ferritin levels were not correlated with the incidence of new-onset LV dysfunction in this cohort. The all-cause mortality rate was also higher in patients with ID, defined by TSAT <20% compared to those with normal TSAT. A subgroup analysis revealed no significant difference in predicting new-onset LV dysfunction between patients with ID, with or without coexisting anemia (P = 0.165). Conclusion: In patients with CAD, ID, particularly defined by TSAT <20%, was predictive of future LV dysfunction and associated outcomes. Further studies are needed to investigate the underlying mechanisms and causal relationship between ID and the risk of LV dysfunction.